Trifarotene Reduces Risk for Atrophic Acne Scars: Results from A Phase 4 Controlled Study - Stephen Schleicher; Angela Moore; Elyse Rafal; Angelique Gagne-Henley; Sandra Marchese Johnson; Sunil Dhawan; Rajeev Chavda; J. P. York; Baldo Sforzolini; Kate Holcomb; Glynis Ablon; James Del Rosso; et al. (Adis, Springer Healthcare, 2023)
Abstract Background Atrophic acne scarring often accompanies acne vulgaris. The efficacy of topical retinoids for treatment of acne is well documented; however, evidence for use in atrophic acne scars is limited. Methods In this randomized, split-face, double-blind study, subjects (age: 17-34 years, N = 121) with moderate-to-severe facial acne, with acne scars present, were treated with either trifarotene 50 μg/g or vehicle once daily for 24 weeks. Efficacy was assessed by absolute and percent change from baseline in atrophic acne scar counts, Scar Global assessment (SGA), and IGA success rates as well as acne lesion counts. Results At week 24, a statistically significantly greater reduction in the mean absolute change from baseline in the total atrophic scar count was noted in the trifarotene- vs vehicle-treated area (− 5.9 vs − 2.7; p < 0.0001) with differences between sides noted as early as week 2 (− 1.5 vs − 0.7; p = 0.0072). The SGA success rate was higher in the trifarotene side at week 12 (14.9% vs 5.0%, P < 0.05) and improved through week 24 (31.3% vs 8.1%, P < 0.001). Similarly, at week 24, the IGA success rate was higher with trifarotene (63.6% vs 31.3%, P < 0.0001) along with reductions in total (70% vs 45%) and inflammatory (76% vs 48%) lesion counts. The incidence of treatment-emergent adverse events was 5.8% (trifarotene) and 2.5% (vehicle); most common (> 1%) was skin tightness (1.7% vs 0.8%), and all events were mild to moderate in severity. Conclusions Trifarotene was effective and well tolerated in treating moderate-to-severe facial acne and reducing atrophic acne scars, with reduction of total atrophic scar count as early as week 2. Trial Registration Clinicaltrials.gov NCT04856904.